Engaging with industry through Design Thinking: Reflections of a WIL educator - Tay, Jo Li Marie-Joelle (2020)
Design thinking has recently gained popularity outside of the design industry, especially in the business sector. Companies are recognising the value that design and design thinking brings, especially in terms of solving problems. The growing interest in design thinking has provided design students with opportunities to engage with industries outside the creative industries sector, such as consulting.